TINJAUAN PSAP BERBASIS AKRUAL PERNYATAAN NO. 5 ATAS AKUNTANSI PERSEDIAAN PADA KEMENTERIAN KOMUNIKASI DAN INFORMATIKA REPUBLIK INDONESIA - Finna Ayuning Putri (2020)
Inventories are current assets in the form of goods obtained with the purpose of being used to support government operational activities or a form of service to the community. Inventories are regulated in Government Accounting Standards Statement No. 5 on Inventory Accounting which aims to support the orderly administration of inventory goods. Inventories are recorded on an accrual basis, that is, records are made at the time of the transaction either at the time of use or when obtaining inventory. This accrual basis can improve efficiency and effectiveness in the accountability of the use of APBN funds. The Ministry of Communication and Information is implementing this PSAP to support transparent and responsible administration of inventories.